Book Review: Heritage Tourism Destinations by Maria D Alvarez (et al.) - Roeland P Paardekooper (EXARC Journal)
This book is a follow-up from the first Hospitality, Tourism and Heritage International Conference, held in Istanbul, Turkey from the 6th to the-7th November 2014. It is wonderful that these papers were published only two years later. This book’s goal is to cross the bridge between theory and conceptual reflections on the one hand and empirical judgements based on fieldwork experience, between the production of heritage tourism attractions and the consumption side of it, the tourists and their backgrounds.